THE INFLUENCES OF PROBLEM BASED LEARNING ACCOMPANYING ANALYZE CASE STUDY TOWARD SCIENTIFIC LITERACY OF STUDENTS - Husna, Fina Rizqotul; Sukaesih, Sri; Setiati, Ning (Journal of Biology Education, 2017)
Biology learning process in SMA N 1 Slawi generally still oriented to the cognitive learning, yet oriented to develop students' scientific literacy skills in context aspects, competence, knowledge, and attitudes of science. This research aimed to describe the effect of the of Problem-Based Learning accompanying Analyze Case Study to develop scientific literacy of students of grade X SMA N 1 Slawi. The research was a quasy experimental research used  non-equivalent control group design. Sampling techniques was purposive sampling method, which the grade of  X MIA 3 as the control class and X MIA 6 as an experimental class. This data research is data scientific literacy test results, student activities, student respons, teacher feedback, and adherence to learning. scientific literacy test data were analyzed using t-test and test of N-gain. The results showed that learning to use the PBL to Analyze Case Study on experimental class significant to the control class scientific literacy test results analysis, t test showed tcount 4.28 >  ttable 1.996 with significance level of 0.05 so it can be seen the difference in the increase the results of the second study classes. Test N-gain in the low category to high, the experimental class has a percentage of 94.12%, 65.71% while the control class. The t-test average score of N-gain with tcount5 > ttable 1.996. Analysis of experimental class student activity is higher than in the control class with the percentage of 84% for the experimental group and 71% of pupils to grade control included in the criteria fairly active and active learning activities. Based on the results of this study concluded that the application of the model of Problem Based Learning to Analyze Case Study positive effect on students' scientific literacy skills.